The Rungus Longhouse of Bavanggazo: Preserving Sabah's Cultural Heritage (LITPAM, 2024)
This study explores the unique cultural heritage of the Rungus people through their traditional longhouses in Bavanggazo, Sabah. It aims to understand how these architectural structures support the preservation of the Rungus language, traditions, and identity amid modernizing influences. Using a qualitative ethnographic approach, data were gathered through interviews and direct observation to capture the lived experiences within these longhouses. The findings highlight the active role of the Rungus language in daily communication, the enduring practice of cultural ceremonies, and the architectural significance of longhouses in sustaining intergenerational heritage. Furthermore, the study discusses factors contributing to the decline of traditional longhouses and the initiatives by the Rungus community to preserve this cultural symbol. By emphasizing the intersection of architecture and cultural sustainability, this research offers insights into the challenges and strategies involved in safeguarding indigenous heritage.